(untitled) (Research, Society and Development, 2021)
This study aims to share a successful experience of using the WhatsApp® application as a therapeutic and pedagogical resource for health education. The resource was used in a group monitoring of smoking cessation in the pandemic scenario of COVID-19 in the context of Primary Health Care (PHC). This is an experience report, developed between the months of June to December 2020 in a Basic Health Unit (UBS) in the interior of Minas Gerias. Through a group with the participation of 10 smokers, abstaining from the use of drug therapy and using strategies applied via WhatsApp®, it was possible for professionals to intervene in the control and / or cessation of smoking by 80% of users. Therefore, Information and Communication Technologies (ICTs) in health care and education, can be complementary tools in professional practice for behavioral changes that favor quality of life and damage prevention, such as those caused by COVID-19.